![((2x + 3) + (x + 5))^2 + ((2x + 3) - (x + 5))^2 = 10x^2 + 92 \\ ((2x + 3) + (x + 5))^2 + ((2x + 3) - (x + 5))^2 = 10x^2 + 92 \\](https://tex.z-dn.net/?f=%28%282x+%2B+3%29+%2B+%28x+%2B+5%29%29%5E2+%2B+%28%282x+%2B+3%29+-+%28x+%2B+5%29%29%5E2+%3D+10x%5E2+%2B+92+%5C%5C+)
answer this if you genius
Answers
Answered by
1
Answer:
x=6/11
Step-by-step explanation:
(2x+3+x+5)² + (2x+3-x-5)²
(3x+8)² + (x-2)²
(9x²+48x+64) + (x²-4x+4)
10x²+44x+68 = 10x²+92
10x²+44x+68-10x²-92 = 0
44x-24=0
11x-6=0
11x=6
x=6/11
Similar questions